Pike in the Kansas Flint Hills, 1806 - Leo E. Oliva (Symphony in the Flint Hills, 2009)
Zebulon Montgomery Pike was the first U.S. Army explorer to cross the present state of Kansas during his 1806-1807 expedition to the American Southwest. Although his primary missions, established for him by General James Wilkinson, were accomplished in other present states (return of Osage Indians to their homes in western Missouri, visit with Pawnee Indians in southern Nebraska, find the source of the Arkansas River in Colorado, and seek the source of the elusive Red River which is in Texas), Pike provided the first published reports on Kansas, the Flint Hills, and the Great Plains.
Keywords: Indians; Anglo-Americans; explorer; rivers; Pike; Osage; Pawnee; Kansas; Flint Hills; Missouri Valley; history; Zebulon Pike